Basic nutrition and diet therapy : laboratory manual for allied health - Caudal, Maria Lourdes Cruz- (Quezon City, Philippines : C & E Publishing Inc., 2019)
This book covers the laboratory component of a one-semester course in nutrition required in the nursing program.
Introduction -- Exercises No. 1. Calculating Diets and Meal Planning -- Exercises No. 2. Macronutrients -- Exercises No. 3. Fat- Water-soluble Vitamins -- Exercises No. 4. Nutrition in the Life Cycle -- Exercise No. 5. Standard Hospital Diets -- Exercise No. 6. Diabetes Diet -- Exercises No. 7. Diets for Gastrointestinal (GI) Disorders -- Exercises No. 8. Diets for diseases of the Liver, Gallbladder, and Pancreas -- Exercises 9. Diets. for renal diseases -- Exercises 10. Diets for Renal Diseases -- Exercises No. 12. Food Preparation and services -- Appendix A-1. Recommended Energy and Nutrients Intakes per Day for Filipinos -- Appendix A-2. Recommended Daily Intakes for Other Minerals and Vitamins -- Appendix B. Guide to Good Nutrition -- Appendix C. Daily Nutritional Guide Pyramid for Filipino Adults -- Appendix D. Suggested Menu for Adults -- Appendix E. Recommended Diet Modifications to decrease Dietary Fat (25 Grams or 50 Grams Fat) -- Appendix F. Medical Nutrition Therapy for diabetes -- Appendix G. Medical Nutrition Therapy to lower cholesterol: Guidelines for Step 1 and Step 2 Diets -- Appendix H. Purine Contents of Different Food Items -- Appendix 1. National Renal Diet -- Appendix J-1. Pork Cuts -- Appendix J-2 Beef Cuts.
Includes bibliographical references.
Keywords: DIET THERAPHY